SISTEM SMART PARKING DI GAIA MALL KUBU RAYA MENURUT KHES PASAL 305 DAN UU PERLINDUNGAN KONSUMEN NO 8 TAHUN 1999 - Rada Nawansari; Rahmat Rahmat; Moh Fadhil (LP2M and Shariah Faculty of The Pontianak State Institute of Islamic Studies, 2024)
The purposes of this study are to find out how the smart parking system is at Gaia Kubu Raya Mall based on KHES article 305 and to find out the smart parking system at Gaia Kubu Raya Mall according to Consumer Protection law number 8 of 1999. The approach that researchers use is a qualitative approach and Juridical Sociological Law. A qualitative approach is research that emphasizes aspects of deepening data in order to obtain quality results of a study. In this study a qualitative approach was used to gather data or information related to the smart parking system at Gaia Kubu Raya Mall. The research results show that the smart parking system according to KHES article 305 is declared invalid because there are conditions that have not been met, namely in a clear description of the goods (size, quantity, shape, etc). business actors do not explain how the smart parking system works so that disadvantaged consumers because the smart parking card work system requires to top up the balance once a month in the amount of IDR 35,000 and the balance will continue to run out whether used or not used with a time limit of one month and the next month continue to fill the balance as usual. smart parking system according to Consumer Protection Act No.8 of 1999 is said to be null and void because the business actor includes a standard clause in the smart parking system so that consumers are harmed.